Resistance training prevents the cardiovascular changes caused by high-fat diet - Speretta, Guilherme F. [UNESP]; Silva, André A. [UNESP]; Vendramini, Regina C. [UNESP]; Zanesco, Angelina [UNESP]; Delbin, Maria A.; Menani, José V. [UNESP]; Bassi, Mirian [UNESP]; Colombari, Eduardo [UNESP]; Colombari, Débora S.A. [UNESP] (Elsevier, 2016)
Aims Aerobic exercise is indicated for prevention and treatment of obesity-induced cardiovascular disorders. Although the resistance training (RT) may also produce effects similar to aerobic exercise, this is not completely clear yet. In the present study, we tested if RT in moderate intensity might prevent alterations in blood pressure (BP), sympathetic modulation of systolic blood pressure (SBP), baroreflex function and the changes in renin-angiotensin system (RAS) and cytokines mRNA expression within the nucleus of the tract solitary (NTS) in rats fed with high-fat diet (HFD). Main methods Male Holtzman rats (300-320 g) were divided into 4 groups: sedentary with standard chow diet (SED-SD); sedentary with high-fat diet (SED-HFD); RT with standard chow diet (RT-SD); and RT with high-fat diet (RT-HFD). The trained groups performed a total of 10 weeks of moderate intensity RT in a vertical ladder. In the first 3 weeks all experimental groups were fed with SD. In the next 7 weeks, the SED-HFD and RT-HFD groups were fed with HFD. Key findings In SED-HFD, BP and sympathetic modulation of SBP increased, whereas baroreflex bradycardic responses were attenuated. RT prevented the cardiovascular and inflammatory responses (increases in tumoral necrosis factor-α and interleukin-1β) produced by HFD in SED rats. The anti-inflammatory interleukin-10, angiotensin type 2 receptor, Mas receptor and angiotensin converting enzyme 2 mRNA expressions in the NTS increased in the RT-HFD compared to SED-HFD. Significance The data demonstrated that moderate intensity RT prevented obesity-induced cardiovascular disorders simultaneously with reduced inflammatory responses and modifications of RAS in the NTS.
Keywords: Baroreflex; Brainstem; Hypertension; Nucleus of the solitary tract; Obesity; Renin-angiotensin system